Prenatal ultrasound manifestations of partial urorectal septum malformation sequence from the first trimester to postnatal: a case report - Lingna She; Hualan Lin; Shuxian Huang; Lina Liu; Liyan Chen (BMC, 2023)
Abstract Background Urorectal septum malformation sequence (URSMS) is characterized by incomplete partitioning of the genital, rectal, and urinary tracts, resulting in a severe form of anorectal malformation. The partial URSMS, also known as the persistent cloaca, represents a milder variant where a single perineal opening serves as a passage for the urinary, gastrointestinal, and reproductive tracts. Case presentation We present a rare case of partial URSMS accompanied by duplicated vagina and uterus, hydronephrosis, ascites, and anal atresia. Conclusions This case report describes the sonographic findings at different stages of pregnancy and their changes throughout gestation.